Premix, Base Mix and Starter Diet Recommendations for Swine - Tokach, Mike D.; Goodband, Robert D.; Dritz, Steve S.; Nelssen, Jim L. (My University, 2002)
This publication contains recommendations for swine diets using premix, base mix, and starter diets.
MF2299_2002_05
Keywords: MF2299; Livestock; MF